VEHICLE NUMBER RECOGNITION AND COUNTING THE NUMBER OF VEHICLES (Journal of Pharmaceutical Negative Results, 2022)
In Today’s world new technologies are coming day by day. And these technologies are reducing the involvement of human and making things easier for us and thus reducing the human labor cost. India is one of the nations with the highest population densities in the world, so a lot of vehicles are there. Consequently, it is necessary to detect automobiles. This system recognises the image of a vehicle's licence plate from video and the number is extracted using various techniques and algorithms. The device can be used at college entrances and other places with strong access restrictions. When a car passes by the system, video is recorded and then transformed into images with the aid of the OpenCV programme.